Dimensions of Legal, Justice and Gender Equality in Education - Abustan, Abustan; Siregar, Hamdan Azhar; Mustomi, Otom (AMCA Journal of Community Development, 2025)
Indonesia is a country based on the rule of law. As a country, with the fourth largest population in the world, the Indonesian state must always pay attention to all citizens in it, including women. The legal dimension provides firm guidance that all human beings, without distinction between women and men, because both are social beings, were created by the Almighty to develop a very important mission as "leaders on earth". Therefore, women and men are expected to work hand in hand, work together to create a just, peaceful, happy and humane society. Of course, with efforts to promote gender-equitable education throughout Indonesia, the aspirations of the nation's founding fathers, namely advancing general welfare, educating the nation's life, and social justice can soon be realized. Writing this paper takes the subject matter related to: Law, Social, and Humanities. By prioritizing the legal dimension of truth (legal truth) in realizing justice (legal justice) for women in the education sector. The purpose of this writing is to find out the legal dimensions related to gender justice, as well as the extent to which the right to educational outcomes supports the attainment of justice. For this reason, empirical research was carried out using a sociological juridical approach.